License to Kill? Domestic Cats Affect a Wide Range of Native Fauna in a Highly Biodiverse Mediterranean Country - Mori, Emiliano; Menchetti, Mattia; Camporesi, Alberto; Cavigioli, Luca; Tabarelli de Fatis, Karol; Girardello, Marco (Frontiers in Ecology and Evolution, 2019)
Amongst domestic animals, cats Felis catus are widely considered as one of the most serious conservation threats for wildlife. This is particularly evident for island ecosystems, as data for the mainland are often lacking. In Italy, the European richest country in biodiversity, cats are very popular as pets. We collected data on impact by cats both through a citizen science approach (wildlife predations by 145 cats of 125 owners) and by following 21 of these 145 cats for one year and recording all the prey they brought home. Domestic cats killed at least 207 species (2042 predation events); among those, 34 were listed as “Threatened” or “Near Threatened” by the IUCN and Italian Red Lists. Birds and mammals such as passerines and rodents were most commonly reported to be killed by free-ranging cats. As to the diet in functional trait space, we observed that the class occupying the largest functional space was that of birds, followed by mammals, reptiles and amphibians. Thus, the largest impact was on the functional structure of mammal and bird communities. The use of a tinkerbell did not affect predation rate by cats, and numbers of prey items brought home decreased with increasing distance from the countryside. We provide evidence that the impact of free-ranging domestic cats may seriously affect the conservation of threatened and non-threatened wildlife species, which already suffer from population declines due to other causes, e.g. habitat loss. The mitigation of impacts by domestic cats on wildlife requires dissemination projects promoting responsible cat ownership, as well as restriction in free‐ranging behaviour, particularly in night time.